Birth Spacing of Pregnant Women in Nepal: A Community-Based Study - Karkee, Rajendra; Lee, Andy H. (Frontiers in Public Health, 2016)
Background Optimal birth spacing has health advantages for both mother and child. In developing countries, shorter birth intervals are common and associated with social, cultural and economic factors, as well as a lack of family planning. This study investigated the first birth interval after marriage and preceding interbirth interval in Nepal. Methods A community-based prospective cohort study was conducted in the Kaski district of Nepal. Information on birth spacing, demographic and obstetric characteristics was obtained from 701 pregnant women using a structured questionnaire. Logistic regression analyses were performed to ascertain factors associated with short birth spacing. Results About 39% of primiparous women gave their first child birth within one year of marriage and 23% of multiparous women had short preceding interbirth intervals (<24 months). The average birth spacing among the multiparous group was 44.9 (SD 21.8) months. Overall, short birth spacing appeared to be inversely associated with advancing maternal age.For the multiparous group, Janajati and lower caste women, and those whose newborn was female, were more likely to have short birth spacing. Conclusions The preceding interbirth interval was relatively long in the Kaski district of Nepal and tended to be associated with maternal age, caste, and sex of newborn infant. Optimal birth spacing programs should target Janajati and lower caste women, along with promotion of gender equality in society.